2017
DOI: 10.1038/s41467-017-00174-7
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic radiation for childhood cancer drives structural aberrations of NF2 in meningiomas

Abstract: Cranial radiotherapy improves survival of the most common childhood cancers, including brain tumors and leukemia. Unfortunately, long-term survivors are faced with consequences of secondary neoplasia, including radiation-induced meningiomas (RIMs). We characterized 31 RIMs with exome/NF2 intronic sequencing, RNA sequencing and methylation profiling, and found NF2 gene rearrangements in 12/31 of RIMs, an observation previously unreported in sporadic meningioma (SM). Additionally, known recurrent mutations chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
56
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 30 publications
8
56
1
1
Order By: Relevance
“…Finally, while novel fusions were recently discovered in a subset of meningiomas, 26,27,33 we did not detect any clinically actionable gene fusions in the meningiomas in our study. This may be explained by the fact that the majority of the cases in our cohort have a low-grade histology, whereas gene fusions, such as those involving TERT (telomerase reverse transcriptase), have been described in high-grade meningiomas.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Finally, while novel fusions were recently discovered in a subset of meningiomas, 26,27,33 we did not detect any clinically actionable gene fusions in the meningiomas in our study. This may be explained by the fact that the majority of the cases in our cohort have a low-grade histology, whereas gene fusions, such as those involving TERT (telomerase reverse transcriptase), have been described in high-grade meningiomas.…”
Section: Discussioncontrasting
confidence: 75%
“…Fusion oncogenes have been described in several human cancers including meningiomas 26,27 and have been successfully targeted in several tumor types. 28 To assess whether clinically targetable gene fusions were present in posterior fossa meningiomas, we performed targeted RNA fusion gene analysis in all samples using Archer FusionPlex and did not detect any relevant RNA fusion transcripts (►Table 1).…”
Section: Gene Rearrangements Are Not Common In Posterior Fossa Meningmentioning
confidence: 99%
“…Two recent studies of radiation- induced meningiomas found that they lacked somatic single nucleotide variants in the most common genes associated with spontaneous meningioma development including NF2 , TRAF7 , AKT1 , SMO , and KLF4 . Instead, they harbored frequent structural rearrangements involving the NF2 tumor suppressor gene, which are only rarely seen in spontaneous meningiomas [1, 28]. Together, these studies provide preliminary evidence that the DNA double-strand breaks caused by ionizing radiation may lead to a distinct genomic signature and gene alterations that drive radiation-induced secondary malignancies.…”
Section: Introductionmentioning
confidence: 94%
“…Meningiomas are more prevalent in female patients, and their incidence increases with the age; malignant tumors are, however, more common in men and children [35,36]. They can also occur secondary to radiotherapy performed for other malignancies [37,38]. Diagnosis is made mainly based on both neurological and radiological evaluation, although the pituitary function can be affected as well.…”
Section: Meningiomas and Chordomasmentioning
confidence: 99%